2020
DOI: 10.3390/en14010077
|View full text |Cite
|
Sign up to set email alerts
|

Multivariable Unconstrained Pattern Search Method for Optimizing Digital PID Controllers Applied to Isolated Forward Converter

Abstract: Most of the traditional PID tuning methods are heuristic in nature. The heuristic approach-based tuned PID controllers show only nominal performance. In addition, in the case of a digital redesign approach, mapping of the heuristically-designed continuous-time PID controllers into discrete-time PID controllers and in case of the direct digital design approach, mapping of the continuous-time plant (forward converter) into the discrete-time plant, results in frequency distortion (or warping). Besides this, nonli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The ride performance of the road preview control strategy was evaluated through a stochastic road profile and the results highlighted the importance of the road preview control strategy, which significantly improves ride performance. A similar approach was recently published by G. Abbas et al [35], who used a similar optimization pattern with the integral squared error (ISE) as their objective function. In that particular study, a low overshoot and fast settling times have been reported.…”
Section: Optimal Tuning Via Genetic Algorithmsmentioning
confidence: 99%
“…The ride performance of the road preview control strategy was evaluated through a stochastic road profile and the results highlighted the importance of the road preview control strategy, which significantly improves ride performance. A similar approach was recently published by G. Abbas et al [35], who used a similar optimization pattern with the integral squared error (ISE) as their objective function. In that particular study, a low overshoot and fast settling times have been reported.…”
Section: Optimal Tuning Via Genetic Algorithmsmentioning
confidence: 99%
“…LFC has been investigated due to the relatively low inertia of these systems [40]. In [41], a multivariate unconstrained pattern search method for the optimization of digital PID controllers applied in an isolated forward converter is studied. Conventional digital PID controllers are considered to be designed based on digital redesign and direct digitalization, adjusted by one of the multivariate name search pattern search methods called the Hooke-Jeeves (H-J) search method; with an excellent performance, output voltage regulation can be ensured.…”
Section: Introductionmentioning
confidence: 99%